Treating Granulomatosis With Polyangiitis Presenting as Mastitis With Rituximab - Yaser ALI; Mohammad KHUDADAH; Maryam ALALI; Smiley GEORGE; Ahmad ABDULSALAM (Archives of Rheumatology, 2019)
Granulomatosis with polyangiitis (GPA) is a rare and complex immune mediated disease, which is a part of the anti-neutrophil cytoplasmic antibodies (ANCA) associated vasculitis.(1) It is characterized by necrotizing granulomatous inflammation of vascular tissue or perivascular area.(1) The disease has a spectrum of manifestations. However, involvement of the breast as an initial presentation of GPA has been described only a few times in the literature.(2,3) Thus, no clear line of management has been established with this rare presentation. A 26-year-old female patient presented with erythematous and tender left breast tissue. After some preliminary investigations, magnetic resonance imaging was sought revealing mastitis with regional heterogeneous non-mass enhancement, associated with thickened overlying skin tissue and edematous, tethered pectoralis muscle, and left axillary lymph nodes. The patient underwent an elective left breast lumpectomy and histopathology of the breast tissue showed discrete and confluent granulomatous lobulitis composed of epithelioid histiocytes, Langhans giant cells and lymphocytes, plasma cells with central abscess formation representing florid suppurative-chronic and granulomatous mastitis, with no evidence of infection, tuberculosis or malignancy (Figure 1). <f1> Further history revealed that she had recurrent problems for shortness of breath, wheezes, dry cough and non-allergic sinusitis, and epistaxis in the past seven years. The patient also noted bilateral thigh pain. Her laboratory results showed positive proteinase 3-ANCA and negative autoimmune serology and inflammatory markers. A nerve conduction study was preformed showing axonal neuropathy, and the diagnosis of mononeuritis multiplex was established. Magnetic resonance imaging of the brain and spine were unremarkable. A positron emission tomography-computed tomography was performed that showed a left anterior lung inflammatory lesion with no evidence of metastasis or other active lesions. With the findings of mononeuritis multiplex, breast tissue biopsy, positive proteinase 3-ANCA, and respiratory symptoms, the diagnosis of GPA was reached. She was started on prednisolone 1 mg/kg for eight weeks. In addition, she was started on 500 mg rituximab weekly for four weeks. After a five-month follow-up, she showed marked clinical response with no relapses. A second cycle of rituximab was to be initiated in one-month time. Granulomatosis with polyangiitis presenting with mastitis is a rare feature and a high index of suspicion is required to reach the diagnosis.(4) The best diagnostic tool is histopathology, supported by specific laboratory investigations, as the imaging findings are non-specific.(4,5) Treatment with rituximab is an alternative option for physicians to consider for younger patients, particularly in the presence of other systemic manifestations. To our knowledge, the use of rituximab in GPA presenting with mastitis has not been documented in the literature. Hence, further research is essential to project the efficacy of this treatment.